Generalist populations formed by generalist individuals: A case of study on the feeding habits of a neotropical stream fish - Neves, Rafaela Carvalho; Borges, Pedro Paulino; Zeni, Jaquelini de Oliveira; Casatti, Lilian [UNESP]; Teresa, Fabrício Barreto (FapUNIFESP (SciELO), 2021)
Aim: We described the diet of the generalist stream fish Knodus chapadae and we tested if the environmental conditions are associated with population’s diet and individual specialization. Methods: We analyzed the stomach contents of 287 individuals from 29 streams from the Brazilian savanna (Cerrado). Results: The instream physical habitat structure, physiochemical conditions, and adjacent land use explained partially the variation in the diet of populations, but not the variation in the individual specialization. Thus, the diet changes observed at populational level were driven by changes in the average composition of the diet of individuals that, in turn, remained generalists along the environmental gradient. Conclusions: Our results show that the trophic opportunism described for small characids was also observed in K. chapadae, whose diet shifts according to changes in environmental conditions. Furthermore, the opportunism expressed at the individual level can explain the trophic plasticity observed on the studied species.
Populações generalistas formadas por indivíduos generalistas: Um caso de estudo sobre os hábitos alimentares de um peixe de riacho neotropical
Keywords: Characidae; Diet; Individual specialization; Intraspecific variation; Trophic niche